Keep the Ball Rolling: Information Diffusion within Large Sports-Related Networks through Social Mediators - Vermeer, S. A. M. (Susan) and Araujo, T. B. (Theo) (Communication & Sport, 2020)
Social media have enabled sports fans to interact with their favourite clubs, players, and fellow fans. By using a sample of over 4.5 million tweets, we applied a social networks approach to examine whether and, if so, how different types of users influence online engagement and patterns of information flow of professional football clubs on Twitter. We focus on five types of social mediators (i.e., key users who connect organizations with their publics): (1) organizational (e.g., teams or players), (2) industry (e.g., competitors or associations), (3) media (e.g., journalists), (4) individual (e.g., fans), and (5) celebrities. Our results indicate that the power of media social mediators—the most traditional mediators—has declined over recent years, and they were negatively associated with engagement on Twitter. Instead, relationships between football clubs and publics were primarily mediated by individual social mediators, for top division clubs in particular. Taken together, scholars and practitioners should recognize the potential impact of social mediators, given that even individuals can function as powerful users in the information diffusion process.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTE5ODQxODY4